Business Strategy Recommendation for Warung Lepak Restaurant Using Quantitative Strategic Planning Matrix (QSPM) - Garthinda, Denna; Aldianto, Leo (The Indonesian Journal of Business Administration, 2012)
Tourism has developed into a major industry and has a strategic role and position of Bandung city development. The development has affected to its culinary business growth. Culinary business environment in the recent time has so many changes and becomes much more competitive. The competitiveness leads to Warung Lepak’s performance loss and causes a decrease in sales. Dealing with current situation, the company should be survive and beats the competition through implementing strategic management which covers all future orientated aspects as provided the Quantitative Strategic Planning (QSPM) method. Quantitative Strategic Planning Matrix (QSPM) is a high-level strategic management approach for evaluating possible strategies. Quantitative Strategic Planning Matrix or a QSPM provides an analytical method for comparing feasible alternative actions. The QSPM approach attempts to objectively select the best strategy using input from other management techniques and some easy computations. This Final Project is trying to apply a strategic management systematically of Warung Lepak to return its performance, based on the strategic management framework. First step are scanning the environment and internal organizational, this step would identify possible opportunities and threats and its internal environment for strengths and weaknesses. The next step is formulating strategy which divides into three-stage decision-making framework. Stage 1 is The Input Stage, stage 2 is The Matching Stage, and stage 3 is The Decision Stage. The frameworks are applicable company such as Warung Lepak and can help strategists identify, evaluate, and select strategies. Based on the QSPM analysis result, a turnaround strategy becomes the most appropriate alternative strategy compared with market penetration and market development strategy. Turnaround strategy is a time based systematic process of stabilizing and revitalizing distressed or underperforming firms through financial, operational, and structural reorganization with the aim of achieving sustainable result. The strategy is appropriate to the company in declining phase.  To be succeed, the implementation of alternative strategy needs the role and responsibility of the owners, socialization, and participation from all employees. The systematic step in the Quantitative Strategic Planning Matrix (QSPM) method makes the choosing processes of alternative strategies at Warung Lepak can be done appropriately, therefore the continuous improvement processes can be done in an effective way. Keywords: Quantitative Strategic Planning Matrix, Turnaround Management, Strategic Management.